The association between statin use and osteoarthritis-related outcomes: An updated systematic review and meta-analysis - Zhang, Zhan; Deng, Chunbo; Ma, Xun; Wu, Qijun; Zhou, Fenghua; Liu, Xueyong (Frontiers in Pharmacology, 2022)
Abstract Objective: Findings among studies evaluating the effect of statin use and OA development, a 2020 meta-analysis of data from 11 observational studies of statin use and osteoarthritis (OA) revealed controversial results. We aimed to determine the associations between statin use and OA-related outcomes in an updated meta-analysis. Methods: The protocol was registered with PROSPERO (CRD42020163983). A systematically literature retrieve was performed in the online databases including PubMed, Cochrane Library, Embase, Web of Science, and Scopus, from inception to June 1, 2022, for clinical studies that compared the effects of statin users vs. non-users on OA-related outcomes risks. Systematic review and meta-analyses were performed to estimate the correlations between statin use and OA-related outcomes. Tendency analysis was also used to estimate dose-response effects. Risk of bias was evaluated with the Newcastle-Ottawa Scale. Results: We included 23 studies involving more than 6,000,000 participants. Statin use was associated with increased OA risk (OR 1.099 [95%CI 1.002-1.206, P=0.045]). Higher statin doses had higher OA risk (simvastatin equivalent daily of >40 mg). OA and related surgery risks were significantly reduced in statin users using antihypertensive drugs (AHDs). No significant differences were seen in other outcomes. Conclusion: This meta-analysis inferred that statin use might be associated with increased OA development, especially at higher doses. The present study highlights the importance of recognizing potential OA risk in the population with long-term and/or high-dose statin use, especially in elderly population. In addition, AHDs are associated with lower OA risk and surgeries in hypertensive statin users. Due to limitations of heterogeneity and confounders, more rigorous studies are needed to define the correlations between statin use and OA-related outcomes. Funding: This study was funded by the Joint Program of Key Research and Development of Liaoning Province of China (No.2020JH2/10300138), and Natural Science Foundation of Liaoning Province (No.20180530044).